'Cranberry Star' - A New University of Florida Caladium Variety - Zhanao Deng (EDIS, 2009)
ENH1105, a 4-page illustrated fact sheet by Zhanao Deng, describes this unique new caladium variety with bright white leaves, green veins, and bright purple spots — its origin, description, tuber production, container forcing, landscape performance, and availability. Includes references. Published by the UF Department of Environmental Horticulture, November 2008.